Octogenarians: Looking closer to a new group of cancer patients - Canhoroz, Mustafa; Kanat, Özkan; Evrensel, Türkkan (My University, 2013)
[Abstract Not Available]
Keywords: estrogen receptor; progesterone receptor; aged; anaplastic carcinoma; breast cancer; breast carcinoma; clinical article; colloid carcinoma; comorbidity; female; human; human tissue; hypertension; letter; mammography; metastasis; triple negative breast cancer